Autologus Stem Cell Transplatation as a Care Option in Elderly Patients. A Review - Fratino, Lucia; Rupolo, Maurizio; Mazzuccato, Mario; Berretta, Massimiliano; Lleshi, Arben; Tirelli, Umberto; Michieli, Mariagrazia (Anti-Cancer Agents in Medicinal Chemistry, 2013)
The ageing population and the increase in life expectancy have put new social and health questions into the public health agenda of western countries. Hematological cancer incidence peaks in older population as a logical consequence of a longer lifespan promoting prolonged exposure to carcinogens and accumulation of genetic alterations. Hematological cancer represents a major cause of mortality in this age group despite recent progress observed in the management of cancer in the general population. Autologous stem cell transplantation (ASCT) represents a therapeutic option in the treatment of a large proportion of lymphomas and multiple myeloma, but their role in the onco-geriatric setting remains an open question, due to the presence of chronic disease. Ageing is characterized by progressive decrements in physiologic reserves and abilities to compensate for physical and/or functional limitations, which increase the risk of developing morbidity and disability. These events explains the extreme diversity of ageing individuals in terms of clinical and functional status. As a consequence, life expectancy in the elderly is influenced not only by the neoplastic diseases itself but also by the various co-morbidities common to this age group. The management of elderly people with hematological diseases potentially curative, should therefore combine both geriatric and tumor assessments. Among the elderly patients identified as being candidates for AHSCT, after the mobilization of progenitor cells from the bone marrow into the peripheral blood, the aphaeresis procedure is the most common method for collecting an adequate number of stem cells. The proper selection of patients may greatly improve the results and the toxicity related to cancer treatment in the elderly. We recommend the adoption of some form of geriatric assessment in the evaluation of any patient who is 70 years and older, this review intends to offer an overview of the state of art in ASCT in elderly patients.
Keywords: Elderly patients